PERBEDAAN FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN ANTARA PERUSAHAAN PERBANKAN DAN NON PERBANKAN (Studi Empiris pada perusahaan keuangan perbankan dan non perbankan tahun 2010-2014 ) - Erma Setiawati; Pardiyanto Pardiyanto; Ifin Aria Efendi (Universitas Muhammadiyah Surakarta, 2016)
The purpose of this study was to analyze the effect of capital structure , profitability , size , liquidity to the company's value in the banking and non-banking companies and the difference. The population in this study were the banking and non-banking companies listed on the Stock Exchange in 2010-2014 .The sampling technique was purposive sampling method . The number of samples in this study on the banking company as much as 105 companies and non-banking companies 138 companies for the period 2010-2014 .The analytical method used was multiple regression analysis and different test t-test with SPSS 22. The resuld of this study indicated that no difference variable capital structure, size, profitability and liquidity of the company's banking and non-banking finance. Keywords : Value of the Company, capital structure , profitability , company size , liquidity .